PENGEMBANGAN MEDIA PEMBELAJARAN BUKU SAKU KELAS IV PADA MATERI KEBERAGAMAN BUDAYA TENTANG RUMAH ADAT DI PULAU JAWA - Dara Ayu Prasetyani; Ari Widyaningrum; Mei Fita Asri Untari (STKIP Subang, 2023)
This research aims to develop pocket book media in elementary schools that is suitable for use and in accordance with Cultural Diversity material about Traditional Houses. The type of research used is R&D with procedural research and development from Borg and Gall which has been modified by Sugiyono with development steps, namely; (1) potential and problems, (2) data collection, (3) product design, (4) design validity, (5) design improvements, (6) product testing. The instrument used in this research was a validation sheet questionnaire. The subjects in this research were 3 validators including 2 expert lecturers and 1 expert teacher. The type of data in this research is descriptive qualitative data. The results of the validation of the learning media questionnaire are in the form of a Pocket Book. Based on the results of the validation of the learning media questionnaire in the form of a Pocket Book by the two validators, the results showed the criteria